El interdominio de los estudios métricos de la información en Iberoamérica y Sudáfrica: Análisis en la base SciELO, 1978-2013 - Lazzarotto Freitas, Juliana [UNESP]; Santiago Bufrem, Leilah [UNESP]; Tannuri de Oliveira, Ely Francina [UNESP]; Cabrini Grácio, Maria Cláudia [UNESP] (My University, 2017)
Metric studies of information are viewed as a field that cuts across several different areas. The present paper is aimed at visualizing the configuration of metric studies of information in papers indexed in the database Scientific Electronic Library Online (SciELO) in the period 1978-2013. A diachronic analysis was conducted of the distribution of the periodic scientific production of these studies to identify the most outstanding authors in the topic, the scientific collaboration network, and the main areas, journals, languages and countries in which the topic is present. The study sample consisted of 768 papers from the SciELO database containing terms related to the field. Output indicators were generated, as well as a matrix with absolute frequencies of co-authored papers. An increase in the number of papers took place in the early 2000s. The 42 most productive authors published 167 papers, representing 21.7 % of the corpus. Sixteen of the most productive authors were Brazilian. Collaboration was outstanding between C. Wanden-Berghe and J. Sanz-Valero, J. A. Araújo-Ruiz and R. Arencibia-Jorge, and C. L. M. Silva and R. R. Guarido Filho. The most prominent journal was the Cuban Journal of Health Sciences Information, classified within the area of Applied Social Sciences, with 24 % prevalence in the corpus. The Health area represented 6 %. The research showed the importance of the Health area in the development of metric studies of information. The present study intends to contribute to the development of methodologies more accurately reflecting the fields of knowledge, pointing to the need for absolute, standardized indicators more thoroughly describing the phenomenon of scientific collaboration.
The interdomain of metric studies of information in Ibero- America and South Africa: An analysis in SciELO database, 1978-2013
Keywords: Analysis of scientific production; Bibliometric indicators; Bibliometrics; Co-authorship in scientific publication; Metric studies of information; SciELO